Integration of Artificial Intelligence (AI) in Learning English Writing in Higher Education - Nurul Aini; Yazid Basthomi (Journal of Learning for Development)
This article presents a conceptual analysis around the integration of Artificial Intelligence (AI) in learning English writing in higher education. AI contributes to helping students find fresh ideas and content for writing, as well as correcting grammar, typos, and punctuation, as well as paraphrasing, and enhancing writing quality. There has been a spate of empirical research conducted by academicians and scholars related to AI in English writing, however, none of them analysed or reviewed the original concept of AI. It is essential then to describe the conceptual underpinnings as it helps teachers and students to make a clear definition and limitation, establish the theoretical foundation, enhance ethical understanding, and set the expectation related to the integration of AI in writing. This conceptual article sketches how AI is accepted and integrated as tools to enhance students’ learning of English writing. This conceptual paper applies a conceptual approach exploring recent literature and previous research on the integration of AI in writing. It focuses on the discussion of the concept of AI, AI integration in the English writing context, and the future expectations of AI in writing.